2019
DOI: 10.1111/bjop.12439
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and fat aftereffects and the role of gender: Implications for body image disturbance

Abstract: Body image disturbancea cause of distress amongst the general population and those diagnosed with various disordersis often attributed to the media's unrealistic depiction of ideal bodies. These ideals are strongly gendered, leading to pronounced fat concern amongst females, and a male preoccupation with muscularity. Recent research suggests that visual aftereffects may be fundamental to the misperception of body fat and muscle massthe perceptual component of body image disturbance. This study sought to establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…The current study is not the first to examine body adaptation in the context of gender. A recent study by Brooks et al (2019a) showed that aftereffects of perceived muscle and fat levels are larger in magnitude when the stimuli (adaptation and test) match the gender of the observer. 5 Although the current study focuses on inferences regarding the neural processing of body stimuli, it may also carry implications for real-world body image issues such as BSSM, especially when combined with the aforementioned results.…”
Section: Discussionmentioning
confidence: 99%
“…The current study is not the first to examine body adaptation in the context of gender. A recent study by Brooks et al (2019a) showed that aftereffects of perceived muscle and fat levels are larger in magnitude when the stimuli (adaptation and test) match the gender of the observer. 5 Although the current study focuses on inferences regarding the neural processing of body stimuli, it may also carry implications for real-world body image issues such as BSSM, especially when combined with the aforementioned results.…”
Section: Discussionmentioning
confidence: 99%
“…The current study is not the first to examine body adaptation in the context of gender. A recent study by Brooks et al (2019) showed that aftereffects of perceived muscle and fat levels are larger in magnitude when the stimuli (adaptation and test) match the gender of the observer 4 . Although the current study focuses on inferences regarding the neural processing of body stimuli, it may also carry implications for real-world body image issues such as BSSM, especially when combined with the aforementioned results.…”
Section: Discussionmentioning
confidence: 97%
“…In addition,Palumbo, Laeng & Tomassi (2013) demonstrated that exposure to typical male or female bodies could cause a shift in the perceived masculinity/femininity of otherwise androgynous-looking bodies. As inBrooks et al, (2019) effects were largest when adaptation stimuli matched the gender of the observer.…”
mentioning
confidence: 88%
“…As we have shown here, estimation accuracies and errors interact with the type of stimuli presented in the experiment, thus illustrating that with increasing diversity in the stimuli, it might not be possible to show an “one-to-one mapping” using the above theories, as estimation decisions might be more complex than previously thought. While it is important to recognize that people have different body sizes, shapes, and other physical characteristics 19 , and that even BMI cut-off points may not capture variations in physiological measurements across cultures 45 , our current approach aims demonstrated that it is possible to capture and quantify some of the multi-dimensional visual characteristics, and it is critical that future work should also harness similar approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Others have also attempted to illustrate the discrepancy of body weight across different ethnic groups 2 , 4 , 11 , 14 , 18 . Several vision scientists 19 25 have adopted a well-controlled visual psychophysics approach, using visual adaptation to investigate the impact of context and exposure on body size and shape misperception. Despite these investigations, more work is needed in order to quantify and delineate the contribution of gender, ethnicity, and identity in parallel.…”
Section: Introductionmentioning
confidence: 99%